Effect of communicating genetic risk of type 2 diabetes and wearable technologies on wearable device-measured behavioural outcomes in East Asians: protocol of a randomised controlled trial - Youngwon Kim; Shan Lou; Brian Chung; Simon Griffin; Ziyuan Chen; Job G Godino; Flora Lai Tung Cheung; Michael Multhaup; Derwin King Chung K C Chan; Harrison Hin Sheung Ho; Tsz Him Timothy Tse; Shiu Lun Ryan Au Yeung; et al. (BMJ Open)
Introduction The communication of information about the risk of type 2 diabetes (T2D) alone has not been associated with changes in habitual behaviours among individuals of European ancestry. In contrast, the use of wearable devices that monitor physical activity (PA) has been associated with behavioural changes in some studies. It is uncertain whether risk communication might enhance the effects of wearable devices. We aim to assess the effects of communicating genetic risk for T2D alone or in combination with wearable device functions on wearable device-measured PA among overweight or obese East Asians.Methods and analysis In a parallel group, randomised controlled trial, 355 overweight or obese East Asian individuals aged 40–60 years are allocated into one of three groups: one control and two intervention groups. Blood samples will be used for estimation of T2D genetic risk and analysis of metabolic risk markers. Genetic risk of T2D will be estimated based on 113 single-nucleotide polymorphisms associated with T2D among East Asians. All three groups receive a Fitbit device. Both intervention groups will receive T2D genetic risk estimates along with lifestyle advice, but one of the intervention groups additionally uses Fitbit’s step goal setting and prompt functions. Questionnaires and physical measurements are administered at baseline, immediately after intervention delivery, and 6 and 12 months post intervention. The primary outcome is time spent in moderate-to-vigorous PA from the Fitbit, which will be assessed at baseline, immediately post intervention, 12 months post intervention and at 6-month follow-up. Secondary outcomes include other wearable device-measured parameters, sedentary time, and sleep, blood pressure, metabolic risk markers, hand grip strength, self-reported PA, fruit and vegetable consumption, smoking, and psychological variables. Between-group differences in the continuous and categorical variables collected at baseline will be examined using Analysis of Variance (ANOVA) and χ2 tests, respectively. A series of linear mixed effects models with fixed effects of time, group and interaction between time and group will be performed, with adjustment for potential confounders.Ethics and dissemination The study protocol has undergone review and received approval from the ethics committee of the University of Hong Kong. Findings from our trial will be disseminated through publication in peer-reviewed research journals and presented at international academic conferences.Trial registration number ClinicalTrials.gov, NCT05524909. https://register.clinicaltrials.gov/ (11 November 2024).